THE USE OF CHART GAME IN TEACHING VOCABULARY TO THE FIFTH GRADERS OF ONE STATE PRIMARY SCHOOL IN BANYUASIN - Risa Anggraini (Journal MELT (Medium for English Language Teaching), 2019)
This study was intended to find out whether or not there was any significant difference between the students who were taught by using chart game and those who were not. The population of this research was the fifth graders of One State Primary School Banyuasin academic year 2018/2019 with the total number of 58 students. For the sample, the writer took two classes by using purposive sampling based on the same amount of students: V A (29 students) and V B (29 students). The method used in this study was quantitative with quasi experimental method design. Then, the data were collected from vocabulary test. Researcher did 10 meetings along the research, 1 meeting for pre-test, 8 meetings for treatment, and the rest 1 meeting for post test. Post test result showed that mean of experimental group was 79.10 and mean of control group was 68.14. After being calculated by using independent sample t-test, it was found that value of t-obtained 5.564. It was higher than the critical value of t-table 2.003. Meanwhile, the values of significant (2-tailed) was .000. It indicated that the null hypothesis was rejected and the alternative hypothesis was accepted. In other words, there was significant difference between the fifth graders who were taught by using chart game and those who were not.